Projetos de vida e relações interpessoais de adolescentes em cumprimento de medida socioeducativa de internação - Coscioni, Vinicius (2017)
This master thesis aims to understand how the interpersonal relationships established by adolescents undergoing socio-educational measure of confinement (AUSEMI) contribute to the elaboration of their purpose of life. It is divided into two studies, the first one theoretical and the second one empirical. The theoretical study is a systematic review of the literature that systematically analyzed 30 reports of empirical researches conducted in Brazil, aiming to characterize the undergoing of socio-educational measure of confinement. The review identified the prevalence of coercive practices over pedagogical practices and stressed the need for researches to investigate the processes resulting from deprivation of liberty. The empirical study is a multiple case study based on the Bioecological Theory of Human Development and it was carried out through four focal groups, which had the participation of 25 AUSEMI between 15 and 19 years old who were confined in the Metropolitan Regions of Espírito Santo and Rio Grande do Sul. The participants conceived their futures from two different perspectives: 1) from purposes of life linked to crime, which included a clear sense of action for the future; and 2) from future expectations related to education, family, and work, but without a sense of action to pursue these expectations. Adolescents who had purposes of life linked to crime tended to be disinterested in technical assistance and in the presence of socioeducational agents, which prevented the performance of socio-educational work which promoted other purposes of life. On the other hand, adolescents who had future expectations related to education, work, and family, enjoyed the presence of the detention centers’ workers, who, along with their families, seemed to promote the motivation for the elaboration of purposes of life unrelated to infractional practices. However, the contact with detention centers’ workers and family members seemed to be ineffective in the elaboration of a sense of action that would enable them to leave the world of crime, which is related to the precariousness of work and the time of family visits promoted in the institutions. The relationships established with the other adolescents, in the opposite direction, seemed to contribute to the elaboration of purposes of life linked to crime, from the exchange of information about the organization of the world of crime, as well as more effective ways of practicing infractions. Interventions to AUSEMI should take into account their current future expectations: 1) to adolescents with purposes of life linked to crime, interventions should present new possibilities of life, far from the world of crime; 2) to adolescents with future expectations related to education, work, and family, interventions should be directed to the development of a future plan of action through which such expectations could be possibly real.